Optimizing the CRISPR/Cas9 system for gene editing in Yarrowia lipolytica - Jianhui Liu; Yamin Zhu; Jin Hou (Engineering Microbiology)
Yarrowia lipolytica is a promising host for producing valuable chemicals owing to its robustness and metabolic versatility. Efficient genome editing tools are essential for advancing its biotechnological applications. Although CRISPR/Cas9 technology has been applied in Y. lipolytica, achieving a consistently high editing performance remains challenging owing to the low homologous recombination efficiency and variability in system components. In this study, we optimized CRISPR/Cas9-mediated genome editing in Y. lipolytica to enhance its editing efficiency. Using the RNA polymerase III promoter SCR1-tRNA for sgRNA expression, we achieved a gene disruption efficiency of 92.5 %. The tRNA-sgRNA architecture enabled a dual gene disruption efficiency of 57.5 %. KU70 deletion in the Cas9 system increased the integration efficiency to 92.5 %, and Rad52 and Sae2 overexpression boosted homologous recombination. The introduction of Cas9D147Y, P411T (iCas9) enhanced the efficiency of both gene disruption and genome integration. This study provides a powerful tool for efficient gene editing in Y. lipolytica, which will accelerate the construction of yeast cell factories.